6d-10=

Simple and best practice solution for 6d-10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6d-10= equation:


Simplifying
6d + -10 = 0

Reorder the terms:
-10 + 6d = 0

Solving
-10 + 6d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 6d = 0 + 10

Combine like terms: -10 + 10 = 0
0 + 6d = 0 + 10
6d = 0 + 10

Combine like terms: 0 + 10 = 10
6d = 10

Divide each side by '6'.
d = 1.666666667

Simplifying
d = 1.666666667

See similar equations:

| 17(t-3)(t-8)=0 | | 15.4+3.5h=1.2h-6 | | 3.3n+3.4=54+6n | | 12d-84= | | -6+15g=9+15g | | 8y-30=34 | | 3(y+2)=y+24 | | 2x+15=14-x | | (-8x+2y)(-4x+4y)= | | c=(3x+y-4)*5-5y+3 | | 5-15t=-15t-14 | | 4+14x=2x-8+12x | | -18n+6n-3=5-12n | | 965.3616=87.92*r^2+62.17*r | | -6y-1=-9y+2 | | 7x-5+3x=75 | | -6-10v=-10v-6 | | w^2-2w=-67 | | -4m+7=7-4m | | 3(p-3)=24 | | -3z-10=-z+10 | | -8r-9=-8r | | 2(x-3)+5(1-x)=2 | | 11m-66-17= | | 5k-9=-9+5k | | 40(9+7x)+3-5x=17 | | 965.3616=87.92*r^2+6.28*r*9.9 | | 2-2u=-2u+2 | | -2x+-1+x= | | 8(j-4)=2(4j-3) | | 0=5b-5b | | 5(5a+2)-4a=0 |

Equations solver categories